2017
DOI: 10.1038/s41598-017-11431-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between Insomnia and Metabolic Syndrome in a Chinese Han Population: A Cross-sectional Study

Abstract: The association between insomnia and metabolic syndrome remains unclear, especially among different-aged groups. A cross-sectional study with 8017 participants was performed to identify whether insomnia was associated with metabolic syndrome or not. Demographic characteristics, lifestyles and other risk factors were collected using a predesigned, semi-structured, self-administered questionnaire, and physical examinations were conducted by certificated community physicians. Insomnia was not independently associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
(63 reference statements)
1
17
0
Order By: Relevance
“…Additionally, insulin resistance may be induced by sleep disorder, including sleep fragmentation or sleep restriction [54,55], which had a significant impact on the development of metabolic syndrome [56]. Accordingly, prolonged sleep deprivation could regulate the impact of glucose metabolism and further develop metabolic syndrome [57]. Our stratified analysis revealed that insomnia symptoms did not significantly influence the association of sleep duration with the components of metabolic syndrome and CRP as reported in the previous study [34], suggesting that there were no differences in the association of sleep duration with metabolic syndrome and inflammation between the individuals with and without insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, insulin resistance may be induced by sleep disorder, including sleep fragmentation or sleep restriction [54,55], which had a significant impact on the development of metabolic syndrome [56]. Accordingly, prolonged sleep deprivation could regulate the impact of glucose metabolism and further develop metabolic syndrome [57]. Our stratified analysis revealed that insomnia symptoms did not significantly influence the association of sleep duration with the components of metabolic syndrome and CRP as reported in the previous study [34], suggesting that there were no differences in the association of sleep duration with metabolic syndrome and inflammation between the individuals with and without insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, available studies used different definition of hypertension, and methodologies for BP measurements (home, office, and rarely ambulatory BP values). Table summarizes the data from large cross‐sectional and longitudinal studies, published over the last 2‐years, assessing the risk of hypertension in patients with insomnia …”
Section: Studies On Insomnia Conducted Over the Last 2 Y Evaluating mentioning
confidence: 99%
“…5,6 With regard to hypertension, few data suggest that both Table 1 summarizes the data from large cross-sectional and longitudinal studies, published over the last 2-years, assessing the risk of hypertension in patients with insomnia. [10][11][12][13][14][15][16] A recently published systematic-review pooled data from 64 clinical studies with diverse designs, including more than 740 000 adults (46.4% male) with insomnia to investigate the relationship between insomnia and hypertension. 17 It was found that when insomnia is frequent, chronic, and accompanied with short sleep or objective indices of arousal, there is a robust link with hypertension.…”
mentioning
confidence: 99%
“…Disturbed sleep, poor sleep quality (short and long sleep durations), and insomnia are not only linked to poor quality of life but also to metabolic syndrome (MetS) and cardiovascular diseases (CVDs); they might be important risk factors for atherosclerosis. [1][2][3][4][5][6][7][8][9][10][11][12] The widely used therapies for sleep disorders and chronic insomnia include medications such as sleeping pills and cognitive behavioral therapy. 13 Sleeping pills can exacerbate or inhibit atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%